Dissecting the function of networks underpinning language repetition - Marcelo L. Berthier; Matthew A. Lambon Ralph (Frontiers Media SA, 2014)
In the 19th century, ground-breaking observations on aphasia by Broca and Wernicke suggested that language function depends on the activity of the cerebral cortex. At the same time, Wernicke and Lichtheim also elaborated the first large-scale network model of language which incorporated long-range and short-range (transcortical connections) white matter pathways in language processing. The arcuate fasciculus (dorsal stream) was traditionally viewed as the major language pathway for repetition, but scientists also envisioned that white matter tracts travelling through the insular cortex (ventral stream) and transcortical connections may take part in language processing. Modern cognitive neuroscience has provided tools, including neuroimaging, which allow the in vivo examination of short- and long-distance white matter pathways binding cortical areas essential for verbal repetition. However, this state of the art on the neural correlates of language repetition has revealed contradictory findings, with some researchers defending the role of the dorsal and ventral streams, whereas others argue that only cortical hubs (Sylvian parieto-temporal cortex [Spt]) are crucially relevant. An integrative approach would conceive that the interaction between these structures is essential for verbal repetition. For instance, different sectors of the cerebral cortex (e.g., Spt, inferior frontal gyrus/anterior insula) act as hubs dedicated to short-term storage of verbal information or articulatory planning and these areas in turn interact through forward and backward white matter projections. Importantly, white matter pathways should not be considered mere cable-like connections as changes in their microstructural properties correlate with focal cortical activity during language processing tasks. Despite considerable progress, many outstanding questions await response. The articles in this Research Topic tackle many different and critical new questions, including: (1) how white matter pathways instantiate dialogues between different cortical language areas; (2) what are the specific roles of different white matter pathways in language functions in normal and pathological conditions; (3) what are the language consequences of discrete damage to branches of the dorsal and ventral streams; 4) what are the consequences (e.g., release from inhibition) of damage to the left white matter pathways in contralateral ones and viceversa; (5) how these pathways are reorganised after brain injury; (5) can the involvement/sparing of white matter pathways be used in outcome prediction and treatment response; and (5) can the microstructure of white matter pathways be remodelled with intensive rehabilitation training or biological approaches.This Research Topic includes original studies, and opinion and review articles which describe new data as well as provocative and insightful interpretations of the recent literature on the role of white matter pathways in verbal repetition in normal and pathological conditions. A brief highlight summary of each is provided below.
English
Keywords: aphasia; temporal lobe; Arcuate Fasciculus; conduction aphasia; ventral stream; language; repetition; dorsal stream